Maquiladoras and informality: A mixed blessing - Benedikt Heid; Mario Larch; Alejandro Ria\~no (Center for Economic Studies and ifo Institute (CESifo), 2011)
Mexico experienced a tremendous expansion of its export-processing maquila sector during the 1990s. At the same time, a large proportion of its labor force remains employed in the informal sector. Since one of the main objectives of the maquiladora program was to increase formal employment, we study how the rapid increase in maquiladora activity has affected labor market outcomes in Mexico. We develop a heterogeneous firm model with imperfect labor markets that captures salient features of the Mexican economy such as the differences between maquila and non-maquila manufacturing plants and the existence of an informal sector. We calibrate the model's parameters to match key cross-sectional moments characterizing the Mexican economy. Our quantitative model indicates that the expansion of the maquila sector during the 1990s produced an increase in informality of 0.9% and a reduction in the skill premium and overall welfare of 2.7% and 3.7%, respectively. A counterfactual experiment in which we shut down the informal sector completely results in a reduction of Mexican welfare of 33.5% relative to the equilibrium with an informal sector.
Keywords: F12; F14; F16; F23; O24; 330; offshoring; informal sector; maquiladoras; trade and labor markets; Mexico; Offshoring; Lohnfertigung; Informeller Sektor; Beschäftigungseffekt; Wohlfahrtseffekt; Mexiko